The moral limits of EU internal market exchange: Equal respect and capabilities - Lyn K.L. Tjon Soei Len (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
The EU's central task is to improve the lives that European citizens are able to live. This mission is embedded in the EU's commitment to enhance the functioning of the internal market on the basis of the assumption that market exchanges form the primary mechanisms through which individuals pursue their own conceptions of the good life. While the EU aims to enable market exchange through its legal structures, it does not consider the demarcation of the moral limits of its internal market as a European task. As such the EU approach to the internal market has so far been based on a decoupling of the market logic from morality. However, justice - as understood in this paper - requires that European citizens are treated with equal respect and that the exchanges they wish to pursue are subject to a generalizable normative standard. This paper explores the question of how and where the moral limits of the internal market are drawn as a question of justice, and argues that the current European approach to this question fails to safeguard European citizens from denigration in the internal market. This discussion paper is part of a series of contributions to the conference "Towards a Grammar of Justice in EU Law', which took place on 6-7 November 2014 at VU University Amsterdam, sponsored by ACCESS EUROPE Amsterdam, VU Centre for European Legal Studies and the Dutch Research Council VENI grant.
Keywords: 320; capabilities; political liberalism; moral limits of the internal market; sexual morality; denigration